Implementasi Kebijakan Perlindungan Anak dalam Penegakan Disiplin Siswa di SMA Mathla'ul Anwar - Feisal Leonard; Sri Handayani; Eva Dianawati Wasliman (STKIP Subang, 2026)
This study aims to analyze the implementation of child protection policies in student discipline at SMA Mathla'ul Anwar Margahayu. Violence in schools remains a critical issue, as indicated by KPAI data showing 226 cases in 2023. This qualitative descriptive study involved interviews with seven informants including school principals, teachers, students, and parents. The findings reveal that the school successfully integrated child protection policies into Student Discipline Standard Operating Procedures through a participatory process adopting positive discipline principles by eliminating physical and psychological violence. The novelty of this research lies in documenting how schools translate macro child protection policies into operational micro practices through three main pillars: structured tiered guidance systems, active roles of the Violence Prevention and Handling Team (TPPK) in prevention, early detection, and case handling, and proactive communication strategies with parents through parenting education and home visits. The study contributes empirical evidence on effective child protection policy implementation in educational settings through appropriate management systems and collective stakeholder commitment.